Influence of normal contact force model on simulations of spherocylindrical particles. Issue 6 (19th January 2018) - Kumar, Rohit; Sarkar, Avik; Ketterhagen, William; Hancock, Bruno; Curtis, Jennifer; Wassgren, Carl
Abstract : How the choice of elastic normal contact force model affects predictions from discrete element method simulations of spherocylindrical particles is investigated in this article. Three force models were investigated: (1) a Hertzian force model (HFM) which assumes a circular contact area; (2) a linear force model (LFM) with a constant stiffness; and (3) a modified HFM (MFM) that accounts for various contact areas and contact transitions. With the MFM, transitions between contact area types must be accounted for otherwise discontinuities in the contact force can occur. It is found that simple force models (HFM, LFM) can be substituted for more accurate force models if only force data and bulk properties are of interest. However, if more detailed contact information, such as contact area, contact overlap, contact duration, or collision frequency, are needed, for example, in population balance models and transient liquid bridge modeling, then a more accurate force model should be used. © 2018 American Institute of Chemical Engineers AIChE J, 64: 1986–2001, 2018